Jenis-Jenis Nyamuk Nokturnal di Perumahan Taman Ciruas Permai, Serang, Banten - Riski Andrian Jasmi; Habil Nursyamsul; Fakhera Shofwa; Annisa Dinda Lestari; Fairuz Dinda Atiyah; Seena Dinda Azzahra; Chicah Dinda Warrohma; Muhammad Dinda Raflie (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to identify the types of nocturnal mosquitoes found in the Taman Ciruas Permai residential area. The method used is sweeping, which involves collecting various mosquito species from the study area and subsequently identifying their morphology in the laboratory. The results show that four mosquito species were found in different numbers: Culex fuscochepala (97 individuals, 38.8%), Culex perexiguus (62 individuals, 24.8%), Culex vishnui (8 individuals, 3.2%), and Aedes aegypti (3 individuals, 1.2%). In conclusion, the Culex genus is the most dominant in the study area, while the Aedes genus was found in much smaller numbers. Keywords: identification, morphology, mosquito, Culex, Aedes.